Correlation Betweeen Skin Fibrosis Based On Modified Rodnan Skin Score And B-Cell Activating Factor Serum In Systemic Sclerosis - Alfarish, M Arzan; Dewi, Sumartini; Hamijoyo, Laniyati; Wachjudi, Rachmat Gunadi (Indonesian Journal of Rheumatology, 2017)
Background: Progression and expansion of skin fibrosis are the most important characteristics in determining clinical responses and prognosis of Systemic Sclerosis(SSc). Using modified Rodnan skin score (mRSS) can not rapidly detect a slight changes of skin fibrosis in SSc patients. Biomarker assessment is needed to make a more objective, quantitative and rapid evaluation of the changes. Suggested potential useful biomarker isB-cell Activating Factor (BAFF), a positive regulator of B cell survival and maturation process. This study aimed to evaluate correlation between skin fibrosis based on mRSS and BAFF serum in SSc patients.Methods: We used cross sectional methods. Enrolled all patients who met ACR EULAR 2013 criteria for SSc in Rheumatology Clinic Hasan Sadikin Hospital, Bandung, from November 2015 to March 2016. Subjects underwent medical record review, physical examination,mRSS measurement by rheumathologist, and blood tests. Data were analized using Rank-Spearman Correlation.Results: Thirty seven subjects, with mean age 40+10 years old. Subjects consisted of 23(62.2%) limited SSc and 14(37.8%) diffuse SSc. Mean BAFF serum was 1160.2+424.7 pg/mL, no statistical difference were found between limited and diffuse type (p=0.662).Median mRSS results was 16 ranged from 2 to 36.Correlation between mRSS and BAFF serum was not significant (r=0.077; p=0.326).Conclusion: There is no correlation between mRSS and BAFF serum in systemic sclerosis at Hasan Sadikin Hospital.Keywords: mRSS, BAFF, Systemic Sclerosis